IMPLEMENTASI WEB SEMANTIK DENGAN APACHE JENA - Bernard Suteja (Informasi Interaktif, 2016)
The information available on the Web can be anything (hypermedia) and about anything. Anybody can be a suspect emergence of false or misleading information. The web site is currently present with no central point of control and can not be used as a central repository. Apache Jena was present to address that fact and can be used in the implementation of semantic web that is easily recognizable by the machine without losing the good things from the web itself as well as the change from a decentralized platform for presentation to a decentralized distribution platform for the distribution of knowledge. In this paper delivered JENA implementation in developing semantic web applications in basic.Keywords : Web, Semantic, JENA